2017
DOI: 10.1038/s41535-017-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced metallization and superconducting phase in ReS 2

Abstract: Among the family of transition metal dichalcogenides, ReS 2 occupies a special position, which crystalizes in a unique distorted lowsymmetry structure at ambient conditions. The interlayer interaction in ReS 2 is rather weak, thus its bulk properties are similar to those of monolayer. However, how compression changes its structure and electronic properties is unknown so far. Here using ab initio crystal structure searching techniques, we explore the high-pressure phase transitions of ReS 2 extensively and pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
58
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 57 publications
12
58
1
1
Order By: Relevance
“…Interlayer coupling widely exists in layered TMDs films, which can greatly influence the properties of layered materials . In some special case, interlayer coupling can induce a phase transition in TMDs.…”
Section: Strategies On Triggering Phase Transition In Tmdsmentioning
confidence: 99%
“…Interlayer coupling widely exists in layered TMDs films, which can greatly influence the properties of layered materials . In some special case, interlayer coupling can induce a phase transition in TMDs.…”
Section: Strategies On Triggering Phase Transition In Tmdsmentioning
confidence: 99%
“…The most common form in TMDs is the H-phase, whereas T-phases are reported to be metastable. However, ReS 2 is an exception, in which the most stable form under ambient condition is a distorted 1T-phase with triclinic symmetry, due to the pronounced Peierls distortion [15][16][17][18][19][20]. Unlike in other TMDs, Peierls distortion of the 1T structure of ReS 2 weakens the coupling interaction, which in turn hinders S-Re-S layers from stacking orderly and minimizes the interlayer overlap of wave-functions to open a band gap (~ 1.4 eV) [15] in the bulk ReS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing studies on MX 2 , the high-pressure behavior of ReS 2 remains largely unexplored until recently [20,30]. Hou et al reported that ReS 2 undergoes a phase transition at about 10.5 GPa based on x-ray diffraction (XRD) patterns analysis [30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations